Convenient Specification Tests for Logit and Probit Models - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 1982)
We propose several Lagrange Multiplier tests of logit and probit models, which may be inexpensively computed by artificial linear regressions. These may be used to test for omitted variables and heteroskedasticity. We argue that one of these tests is likely to have better small-sample properties, supported by several sampling experiments. We also investigate the power of the tests against local alternatives. The analysis is novel because we do not require that the model which generated the data be the alternative against which the null is tested.
Keywords: C12; 330; binary response model; LM test; logit; probit